2021
DOI: 10.1186/s12951-021-00880-x
|View full text |Cite
|
Sign up to set email alerts
|

NIR responsive tumor vaccine in situ for photothermal ablation and chemotherapy to trigger robust antitumor immune responses

Abstract: Background Therapeutic tumor vaccine (TTV) that induces tumor-specific immunity has enormous potentials in tumor treatment, but high heterogeneity and poor immunogenicity of tumor seriously impair its clinical efficacy. Herein, a novel NIR responsive tumor vaccine in situ (HA-PDA@IQ/DOX HG) was prepared by integrating hyaluronic acid functionalized polydopamine nanoparticles (HA-PDA NPs) with immune adjuvants (Imiquimod, IQ) and doxorubicin (DOX) into thermal-sensitive hydrogel. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…[14] In tumor therapy, tumor-specific immunityinducing NP near-infrared (NIR) irradiation delivers tumor antibodies and antigenic vaccines to stimulate local and systemic immune responses to induce the removal of cancer cells. [15,16] Light-responsive nanomaterials are not only used as drug delivery in hydrogels but also have a wide range of antimicrobial properties, and tumor cell ablation via photothermal reaction. [17,18] Light-responsive nanomaterials can be further incorporated inside hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In tumor therapy, tumor-specific immunityinducing NP near-infrared (NIR) irradiation delivers tumor antibodies and antigenic vaccines to stimulate local and systemic immune responses to induce the removal of cancer cells. [15,16] Light-responsive nanomaterials are not only used as drug delivery in hydrogels but also have a wide range of antimicrobial properties, and tumor cell ablation via photothermal reaction. [17,18] Light-responsive nanomaterials can be further incorporated inside hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al constructed a polydopamine (PDA)-based core–shell nanoplatform loaded with CpG ODNs that has a remarkable synergistic treatment effect on inducing the maturation of DCs and the activation of T cells when combined with PTT [ 24 ]. Our previous studies reported a novel NIR-responsive in situ tumour vaccine (HA-PDA@IQ/DOX HG) that promoted DC maturation, memory T-cell generation in lymph nodes and cytotoxic T lymphocyte production in the spleen after photothermal ablation [ 25 ]. However, the techniques used in these studies suffer from many bottlenecks, such as complex preparation, insufficient time and inefficient immune activation.…”
Section: Introductionmentioning
confidence: 99%
“…Ensuring the O 2 transport stability and rapidity of release was the key aspect for PFCs—based O 2 carrier. It has been reported the near-infrared (NIR)-induced photothermal therapy (PTT) not only could kill the tumor [ 28 30 ], but also accelerate O 2 release from PFCs—based O 2 carrier to mitigate tumor hypoxia with remarkably synergistic effects [ 31 , 32 ]. Therefore, sealing off the oxygen in a nanosystem and release it by NIR may be a strategy for delivering O 2 to tumor.…”
Section: Introductionmentioning
confidence: 99%